2021
DOI: 10.1021/acssuschemeng.1c04593
|View full text |Cite
|
Sign up to set email alerts
|

The Performance of Ruddlesden–Popper (R-P) Structured Pr2–xSrxNi0.2Mn0.8O4 for Reversible Single-Component Cells

Abstract: In view of high catalytic activity and oxygen vacancy concentration, Ruddlesden−Popper (R-P) structure oxide has been widely used as the electrode material for solid oxide fuel cells (SOFCs). Herein, three R-P structure oxides, Pr 2−x Sr x Ni 0.2 Mn 0.8 O 4 (x = 1, 1.2, and 1.5), are used as the semiconductor materials of single-component cells. The materials for the oxygen side are hybrid oxides consisting of R-P structure oxide and perovskite oxide. The hydrogen side was exposed to the reduction atmosphere b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 53 publications
0
23
0
Order By: Relevance
“…The details have been described in our previous work. 27 PSCFM11, PSCFM27, or PSNFM27 was first pressed into rectangular bars of 25 × 7.0 × 2.0 mm 3 and then calcined in air at 1250 °C for 6 h. When measuring the conductivities of R-PSCFM11, R-PSCFM27, and R-PSNFM27 in 5% H 2 atmosphere, PSCFM11, PSCFM27, and PSNFM27 were first pretreated in a hydrogen stream at 700 °C for 2 h, then switched to 5% H 2 , and held for 2 h.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The details have been described in our previous work. 27 PSCFM11, PSCFM27, or PSNFM27 was first pressed into rectangular bars of 25 × 7.0 × 2.0 mm 3 and then calcined in air at 1250 °C for 6 h. When measuring the conductivities of R-PSCFM11, R-PSCFM27, and R-PSNFM27 in 5% H 2 atmosphere, PSCFM11, PSCFM27, and PSNFM27 were first pretreated in a hydrogen stream at 700 °C for 2 h, then switched to 5% H 2 , and held for 2 h.…”
Section: Methodsmentioning
confidence: 99%
“…In addition, the electrical conductivities of PSCFM11, PSCFM27, and PSNFM27 in air atmosphere and those of R-PSCFM11, R-PSCFM27, and R-PSNFM27 in 5% H 2 atmosphere were measured by the four-probe method. The details have been described in our previous work . PSCFM11, PSCFM27, or PSNFM27 was first pressed into rectangular bars of 25 × 7.0 × 2.0 mm 3 and then calcined in air at 1250 °C for 6 h. When measuring the conductivities of R-PSCFM11, R-PSCFM27, and R-PSNFM27 in 5% H 2 atmosphere, PSCFM11, PSCFM27, and PSNFM27 were first pretreated in a hydrogen stream at 700 °C for 2 h, then switched to 5% H 2 , and held for 2 h.…”
Section: Experimental Sectionmentioning
confidence: 99%
“…(1) The morphology of carbonate changes during the electrolysis process. Previous research has found that the morphology of carbonate in RSCC gradually becomes lumpy and flake during the operation process . (2) Carbonate may be partially decomposed during operation .…”
Section: Resultsmentioning
confidence: 99%
“…Sm 0.2 Ce 0.8 O 2 -(Li/Na) 2 CO 3 (SDC-LN) as an ionic conductor was prepared by ball milling and the weight ratio of SDC and LN was 7:3. The preparation processes of SDC and LN and the fabrication of SCFC and RSCC have been reported in our previous work. , …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation